Pengaruh Financial Literacy, Financial Behavior Dan Financial Attitude Terhadap Perilaku Konsumtif Dengan Peran Disiplin Keuangan Sebagai Variabel Moderasi - Isrofa Ayu Murni; Tries Ellia Sandari (Jurnal Akuntan Publik, 2025)
The paragraph discusses consumptive behavior, defined as the tendency to exceed basic needs and financial capabilities in consuming goods and services. Many undisciplined students face challenges in managing their finances due to this behavior. The research aims to examine the influence of Financial Literacy, Financial Behavior, and Financial Attitude on Consumptive Behavior, with Financial Discipline as a moderating variable. The study involves 200 respondents, including international students from various universities. Results reveal that financial literacy and financial behavior significantly impact consumer behavior, while financial attitudes do not. Additionally, the moderating role of financial discipline does not affect the relationship between these factors and consumer behavior.